(untitled) (Medico Legal Update, 2020)
Leptin it is a protein hormone containing 167 amino acids, firstly discovered in 1994 by Jeffrey M. Friedman, It is secreted by adipocytes and has been found to regulate food intakes through central neuroendocrine mechanisms. Resistin has been found to be generated and released via adipose tissue to serve endocrine functions which are likely to be associated with insulin resistance. Aim: The aim of this study determination of leptin and resistin hormone level in serum of male and female with type 2 diabetic patients and healthy control in Iraq. Subject and Method: This respective study carried out at three main medical facilities in Baghdad; National Center For Teaching Laboratories, Poisoning Consultation Center/Specialized Surgeries Hospital and the National Blood Transfusion center in Medical City,Iraq during the period from November 2019 to February 2020. It was included 100 participants; divided into 2 groups(50 patient with type 2 diabetes and 50 healthy control). Results: The result of serum leptin showed that there was highly significant difference when comparing the mean of total serum leptin of patient group with that of the control group. While the mean of total circulating resistin in T2DM patient and healthy with no significant difference between the two groups. Conclusion: Increased serum leptin level in type 2 diabetes patient than healthy control and no significant difference in serum resistin level when compared between diabetics and control